IMPLEMENTASI PROFIL PELAJAR PANCASILA DALAM MEWUJUDKAN NILAI KEBHINEKAAN PESERTA DIDIK DI SMK N 6 SEMARANG - Mardarena, Claudia Apriliana; Suneki, Sri (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
This research analytically looks at the applicability of the Pancasila student profile in emphasising his personality based on Pancasila values. In addition, it is important to know the importance of diversity in the profile of Pancasila students. This is because consideration of the value of diversity among these students should understand the diversity of values, for example, the value of democracy, the value of justice and love for the country in the school environment and society, so that students can understand the importance of the value of diversity and the value of diversity. The type of research used is descriptive qualitative. The methods used to collect data are interviews, observation, and documentation. The validity of this research data is the source triangulation technique. Data analysis techniques include data collection, data reduction, presentation, and conclusions. The results showed that the Pancasila Education Teacher, in designing the value of diversity in this lesson, really made and applied the profile of Pancasila students with the diversity of culture in Indonesia and the flow of the purpose of this value of diversity using the culture that exists among schools. Teachers analyse learning motivation in terms of the value of diversity before the activity takes place and the factors that affect student learning motivation at school. Teachers take steps referring to learning outcomes, objectives, models, and strategies. Teachers conduct evaluations to see the achievement of goals and the success of students to increase learning motivation in the value of diversity and the application that students always emphasise